Investigation of insect olfactory receptor modulation - Lee, Sydnie Ting Ying (Nanyang Technological University, 2024)
P4-ATPases have recently emerged as a target for structural studies due to their roles in cellular function. These enzymes actively transport phospholipids from the exoplasmic leaflet to the cytosolic leaflet of eukaryotic membranes, establishing and regulating lipid composition asymmetry between the two leaflets of the membrane bilayer. This asymmetry plays a crucial role in various cellular processes, including vesicle budding, cell signalling, and apoptosis, among others. In Drosophila melanogaster, olfactory receptors play a vital role in odorant perception and are modulated by several olfactory sensory neuron (OSN) proteins and non-OSN proteins. Intriguingly, recent studies have implicated flippases as crucial players in olfactory receptor expression and odorant sensitivity regulation in Drosophila melanogaster. P4-ATPases, being large membrane proteins forming heteromeric complexes, present several challenges for in-vitro studies and structural determination. Here, we investigate the structural and biochemical characterisation of the P4-ATPase dATP8B, a flippase in Drosophila, and its interaction with the chaperone protein dCDC50A. Initial analysis revealed large unstructured N- and C-terminal regions in dATP8B, hypothesized to contribute to instability and purification challenges. To address this, new constructs were designed with targeted deletions of these unstructured regions. Our findings demonstrate that flippase and dCDC50A in Drosophila melanogaster forms a tight and stable complex.